2013
DOI: 10.1159/000351032
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor Receptor Beta Serum Concentrations during First-Line Therapy in Ovarian Cancer

Abstract: Objectives: Angiogenesis plays an important role in ovarian cancer. The interaction of platelet-derived growth factor receptor-beta (PDGFR-β) with vascular endothelial growth factor (VEGF) in the process of angiogenesis may represent an essential feature in the progression of the disease. Methods: Patients with epithelial ovarian cancer, who underwent primary surgery and platinum-based first-line chemotherapy, were included. A total of 133 serum samples from 39 patients were analyzed. Samples were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…PDGFR-α overexpression has been observed in metastatic medulloblastoma patient samples, compared with non-metastatic patient samples, and the disruption of PDGFR-α function inhibited the metastatic potential of medulloblastoma cells in vitro [5]. Mathey et al [6] also found that PDGFR-β could be important as an antiangiogenic agent and has since become a component of the standard treatment in ovarian cancer. Furthermore, PDGFR expression levels are associated with the angiogenesis, invasion and metastasis of colon cancer [79].…”
Section: Introductionmentioning
confidence: 99%
“…PDGFR-α overexpression has been observed in metastatic medulloblastoma patient samples, compared with non-metastatic patient samples, and the disruption of PDGFR-α function inhibited the metastatic potential of medulloblastoma cells in vitro [5]. Mathey et al [6] also found that PDGFR-β could be important as an antiangiogenic agent and has since become a component of the standard treatment in ovarian cancer. Furthermore, PDGFR expression levels are associated with the angiogenesis, invasion and metastasis of colon cancer [79].…”
Section: Introductionmentioning
confidence: 99%
“…These covariates were selected because of their role in BBB/pericyte pathophysiology along with CVA development. 13 , 22 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of PDGFR-α has been observed in metastatic medulloblastoma patient samples, compared with non-metastatic patient samples, in which the disruption of PDGFR-α function inhibited the metastatic potential of medulloblastoma cells in vitro (29). Mathey et al (30) also found that PDGFR-β may be important as an anti-angiogenic agent and has now become a component of the standard treatment of ovarian cancer. Furthermore, the expression levels of PDGFR are associated with the angiogenesis, invasion and metastasis of colon cancer (31)(32)(33).…”
Section: A B Discussionmentioning
confidence: 99%